2019
DOI: 10.1123/ijsnem.2018-0386
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Tool for Managing Performance Nutrition: The Athlete Food Choice Questionnaire

Abstract: This study aimed to develop and refine an Athlete Food Choice Questionnaire (AFCQ) to determine the key factors influencing food choice in an international cohort of athletes. A questionnaire that contained 84 items on a 5-point frequency scale was developed for this study. Athletes at the 2017 Universiade, in Taiwan, were invited to participate. Principal component analysis was utilized to identify key factors and to refine the questionnaire. Completed questionnaires were received from 156 athletes from 31 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…There was a trend to mention macronutrients (particularly carbohydrate and protein) having an influence on their food selection. This is supported by literature that suggests performance factors are important in decisions around food choice in this environment [15,24] but may be less relevant once the competition is over. We found that core food content and fibre was greater in meals prior to competition than post, with a number of athletes mentioning that they were choosing vegetables or ‘greens’.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…There was a trend to mention macronutrients (particularly carbohydrate and protein) having an influence on their food selection. This is supported by literature that suggests performance factors are important in decisions around food choice in this environment [15,24] but may be less relevant once the competition is over. We found that core food content and fibre was greater in meals prior to competition than post, with a number of athletes mentioning that they were choosing vegetables or ‘greens’.…”
Section: Discussionsupporting
confidence: 55%
“…Alternatively, other factors such as sensory appeal and usual eating practices may take priority over performance, as was suggested in some of the reasons for food selection (Table 4). Interestingly, we found some additional reasons for food selection that differed from those identified in a similar cohort of athletes [24]. These were predominately related to physiological considerations, such as hunger, satiety and gut comfort.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Factors influencing the food choice of athletes were collected using the AFCQ [10], which has undergone initial validation testing for internal reliability, face and content validity. An additional 11 items based on the existing literature and relevant to this study were included as stand-alone factors [5][6][7][8][9].…”
Section: Measurement Instrumentmentioning
confidence: 99%
“…These studies have used a range of methods to report on food choice including self-developed questionnaires, focus groups and interviews. More recently, a tool has been developed and validated to measure the ranking of determinants of food choice in athletes (Athlete Food Choice Questionnaire (AFCQ) [10]). Factors included in the survey are the nutritional attributes of the food, emotional influences, food and health awareness, the influence of others, usual eating practices, weight control, food values and beliefs, sensory appeal and performance.…”
Section: Introductionmentioning
confidence: 99%